Neural-humoral responses during head-up tilt in healthy young white and black women - Jarvis, Sara S.; Shibata, Shigeki; Okada, Yoshiyuki; Levine, Benjamin; Fu, Qi (Frontiers in Physiology, 2014)
Young black women have higher prevalence of hypertension during pregnancy compared to white women, which may be attributable to differences in blood pressure (BP) regulation. We hypothesized that young normotensive black women would demonstrate augmented muscle sympathetic nerve activity (MSNA) and renal-adrenal responses to orthostasis. Fifteen white and ten black women (30±4 vs. 32±6 yrs; means±SD) had haemodynamics and MSNA measured during baseline (BL), 30° and 60° head-up tilt (HUT), and recovery. Blood was drawn for catecholamines, direct renin, vasopressin, and aldosterone. BL brachial systolic BP (SBP: 107±6 vs. 101±9 mmHg) and diastolic BP (DBP: 62±4 vs. 56±7 mmHg) were higher in white women (both p< 0.05). ΔDBP (60° HUT-BL) was greater in black women compared to white (p< 0.05). Cardiac output and total peripheral resistance was similar between groups. MSNA burst frequency was higher in whites (BL: 16±10 vs. 14±9 bursts/min, p< 0.05) and increased in both groups during HUT (60°: 39±8 vs. 34±13 bursts/min, p< 0.05 from BL). Noradrenaline was higher in white women (BL: 210±87 vs. 169±50 pg/ml; 60° HUT: 364±102 vs. 267±89 pg/ml, p< 0.05). Direct renin was higher and vasopressin and Δaldosterone tended to be higher in blacks (BL, direct renin: 12.1±5.0 vs. 14.4±3.7 pg/ml, p< 0.05; BL, vasopressin: 0.4±0.0 vs. 1.6±3.6pg/ml, p=0.065; Δaldosterone: -0.9±5.1 vs. 3.8±7.5 ng/ml; p=0.069). These results suggest that young normotensive white women rely on sympathetic neural more so than black women who have a tendency to rely on the renal-adrenal system to regulate BP during an orthostatic stress.